PENGARUH PEER GROUP TERHADAP HASIL BELAJAR SISWA KELAS XII IPS SMA ADVENT TOMPASO TAHUN AJARAN 2020/2021 PADA MATA PELAJARAN SOSIOLOGI - Samuel Rondor; Maryam Lamadirisi; Yoseph Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
This study aims to see whether is an influence of peer groups on student learning outcomes. The research method used is quantitative methods. The collection uses questionnaire and documentation. Based on the study, was found results of a simple regression analysis from the peer group on the learning outcomes of class XII Social Studies students at the Tompaso Adventist High School for the 2020/2021 academic year in the sociology subject obtained a constant (a) 76.026, coefficient value (b) 0.136 which if in the simple regression equation Y = 76.026 + 0.136X, with tcount 2.055 > ttable 2.035 with significance of 0.048 (4.8%) less than 5% that found result there there influence of peer group on the learning outcomes. It was found from the results of questionnaires, learning outcomes, and analysis, turns out that peer group has a role as well but not always make the same result, those are said in poor relationships turn out have high learning outcomes and for them friendship is friendship, be their encouragement to be better or in academics even though they like that but they encourage each other in a good direction, those who are in good relationships as well, as evidenced by the high learning outcomes.